2016
DOI: 10.1007/s00216-016-9436-9
|View full text |Cite
|
Sign up to set email alerts
|

3D Raman imaging of systemic endothelial dysfunction in the murine model of metastatic breast cancer

Abstract: It was recently reported in the murine model of metastatic breast cancer (4T1) that tumor progression and development of metastasis is associated with systemic endothelial dysfunction characterized by impaired nitric oxide (NO) production. Using Raman 3D confocal imaging with the analysis of the individual layers of the vascular wall combined with AFM endothelial surface imaging, we demonstrated that metastasis-induced systemic endothelial dysfunction resulted in distinct chemical changes in the endothelium of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…the 4%‐decrease in the lipid level and the 18%‐increase in the protein content compared with the control. These changes, observed in the endothelium, indicated that it could be a good target in the diagnosis of endothelial dysfunction associated with metastatic breast cancer . To confirm that, HCA was applied to classify the spectra of the endothelium of the control animals and mice with developed cancer metastasis (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…the 4%‐decrease in the lipid level and the 18%‐increase in the protein content compared with the control. These changes, observed in the endothelium, indicated that it could be a good target in the diagnosis of endothelial dysfunction associated with metastatic breast cancer . To confirm that, HCA was applied to classify the spectra of the endothelium of the control animals and mice with developed cancer metastasis (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…An important factor for diseases determination is also time, necessary for obtaining the information about the sample and analysis of this information. Encouraged by our previous results related to pathology investigations using Raman imaging in this work, we decided to check if Raman spectroscopy is indeed such a potent diagnostic tool to study the condition of endothelium. Therefore, we extracted 50–70 random, single, recorded in 0.2 s, spectra from the endothelium of mice with diseases and control animals and subjected them to HCA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments were performed in vivo in the murine 4T1 breast cancer model [34][35][36]. Plasma samples obtained from the blood of 4T1-treated mice and untreated mice were analyzed by ELISA for soluble F11R/JAM-A (sJAM-A) quantitation.…”
Section: Tβ4 and Tgf-β Reduce The Plasma Level Of Soluble F11r/jam-amentioning
confidence: 99%